Współczesne koncepcje ewidencji aktywów zgodnie z Międzynarodowymi Standardami Rachunkowości - Leont'eva, Zamila; Samochin, Jurij (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
This article is devoted to the consideration of the changes in the methodology of accounting for assets, caused by the implementation of IFRS in Russia. The conclusions of the comparative analysis for conceptual differences in accounting approaches to asset valuation under IFRS and Russian accounting standards and reasons for them are presented. Among questions raised there are major peculiarities of accounting and financial reporting for property, plant and equipment, including initial measurement, depreciation policies, accounting for modernization and overhaul costs. Attention is paid to the issues of accounting for intangible assets such as research and development costs and goodwill. The article views the specific features of application of IFRS approach in Russia related to the implementation of IAS 36 "Impairment of Assets", including the peculiarities for defining the right discount rate and indications that an asset may be impaired. The necessity to take into account the changes within IFRS themselves is emphasized, particularly the recent changes caused by the introduction of IFRS 3 "Business Combination". The article analyses the causes for differences in the quality of financial information on assets under IFRS and Russian accounting standards and suggests the ways for necessary improvements and harmonization. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1082, s. 202-207